Peningkatan Keterampilan Menulis Surat Resmi Siswa Melalui Model Pembelajaran Think Pair Share (TPS) di Sekolah Dasar - Shafa Nisa Al-Iman, Shafa Nisa Al-Iman; Fahmi Surya Adikara, Fahmi Surya Adikara; Esti Susiloningsih, Esti Susiloningsih (Jurnal Didaktika Pendidikan Dasar, 2025)
The purpose of this study was to improve the writing skills of grade V students on official letter material. This study used Kemmis and Mc. Taggart model. Each cycle was carried out in one learning activity with a duration of 2x35 minutes. The research was conducted in class V.C, totaling 31 students with details of 13 male students and 18 female students. Based on the results of observations made at State Elementary School 11 Indralaya, Ogan Ilir Regency, data obtained that grade V students still often make mistakes in writing official letters. An alternative solution to the problem is the application of the Think Pair Share type Cooperative Learning model. The results showed an increase in student learning outcomes with an average student score in cycle I of 73.8 and increased to 91.08 in cycle II.  Writing skills can be seen from the final score in cycle I, the percentage of learning completeness exceeded the Minimum Completion Criteria of 74.07% with good qualifications and cycle II increased to 100% with very good qualifications. Therefore, the application of the Cooperative Learning type Think Pair Share learning model can improve the ability to write official letters of grade V students.